Distribution of trace metals in the sediments of Elefsis Gulf - MAVRAKIS, A.; THEOHARATOS, G.; ASIMAKOPOULOS, D.N.; CHRISTIDES, A. (Mediterranean Marine Science, 2004)
The present work examines the temporal evolution of industrial contamination in sediments caused by trace metals in the Elefsis Gulf, Greece. The current state of contamination as well as the related sources can be obtained from the study of the sediments. Trace metals, namely Ni, Cu, Fe, and Mn, were collected during 1984-2003 by the local monitoring network. The statistical analysis of the data and the contaminants isopleths patterns support the following conclusions: There is a strong correlation between the nearby coastal industrial activities and the distribution of the trace metals’ concentration in sediments. There is no seasonal or annual variation of the distribution. The sediments’ concentration of Mn in all sampling points and Cu in the center of the Gulf has decreased during the last years.